Endemic Human Coronavirus-Specific Nasal Immunoglobulin A and Serum Immunoglobulin G Dynamics in Lower Respiratory Tract Infections - Ferdyansyah Sechan; Katherine Loens; Herman Goossens; Margareta Ieven; Lia van der Hoek (Vaccines, 2024)
Endemic human coronaviruses (HCoV) NL63, 229E, OC43, and HKU1 cause respiratory infection. Following infection, a virus-specific serum antibody rise is usually observed, coinciding with recovery. In some cases, an infection is not accompanied by an immunoglobulin G (IgG) antibody rise in serum in the first month after HCoV infection, even though the infection has cleared in that month and the patient has recovered. We investigated the possible role of nasal immunoglobulin A (IgA). We measured spike (S) and nucleocapsid (N)-specific nasal IgA during and after an HCoV lower respiratory tract infection (LRTI) and compared the IgA responses between subjects with and without a significant IgG rise in serum (IgG responders (n = 31) and IgG non-responders (n = 14)). We found that most IgG responders also exhibited significant nasal IgA rise in the first month after the infection, whereas such an IgA rise was lacking in most IgG non-responders. Interestingly, the serum IgG non-responders presented with a significantly higher nasal IgA when they entered this study than during the acute phase of the LRTI. Our data suggest that nasal IgA could be part of a fast acute response to endemic HCoV infection and may play a role in clearing the infection.